Continuity, Naturalism, and Contingency: A Theology of Evolution Drawing on the Semiotics of C. S. Peirce and Trinitarian Thought - Robinson, Andrew J. (Zygon, 2004)
The starting point for this article is the question of the relationship between Darwinism and Christian theology. I suggest that evolutionary theory presents three broad issues of relevance to theology: the phenomena of continuity, naturalism, and contingency. In order to formulate a theological response to these issues I draw on the semiotics (theory of signs) and cosmology of the American philosopher Charles Sanders Peirce. Peirce developed a triadic theory of signs, underpinned by a threefold system of metaphysical categories. I propose a semiotic model of the Trinity based on Peirce's semiotics and categories. According to this model the sign-processes (such as the genetic “code”) that are fundamental to life may be understood as vestiges of the Trinity in creation. I use the semiotic model to develop a theology of nature that addresses the issues raised by evolutionary theory. The semiotic model amounts to a proposal for a new metaphysical framework within which to understand the relationship between God and creation and between theology and science.